A DFT Study of the Conversion of Ptaquiloside, a Bracken Fern Carcinogen, to Pterosin B in Neutral and Acidic Aqueous Medium. Issue 26 (18th September 2017) - Ríos‐Gutiérrez, Mar; Domingo, Luis R.; Alonso‐Amelot, Miguel E.
Abstract: The conversion of ptaquiloside (PtQ), a bracken fern ( Pteridium aquilinum ) carcinogen, to pterosin B (PtB), which is involved in the underlying mechanisms of PtQ genotoxicity and carcinogenicity, has been theoretically studied in aqueous neutral (AN) and acid (AA) media, using DFT methods at the PCM(water)‐B3LYP/6‐31G(d)//B3LYP/6‐31G(d) computational level. The β ‐elimination of glucose in AN and four reactive channels ( A‐D ) defined by as many protonation sites in PtQ were calculated. Activation enthalpy decreases (from 42.0 to 12.6 kcal mol −1 ) in AA relative to AN suggesting protic catalysis. The most favoured channel A started with protonation of the tertiary O 15 hydroxyl of PtQ and SN 1 water release with strong stabilisation by the spirocyclopropane ring. Natural population analysis and electron localisation function analysis showed significant electron depopulation of vicinal C−C bonds and the remarkable leaving character of the quaternary carbon, which enhanced the nucleophilic attack of water on the distal methylenes while the glucose fragment was retained. This intermediate was unstable, degrading rapidly to a stable PtB‐glucose‐water‐H + molecular complex whose calculated electronic spectrum (λmax =271.5 nm) matched the value of an intermediate reported earlier with a different structure. PtQ‐dienone, long assumed as the carcinogenic form of PtQ, is not formed in AA but only and unfavourably so in protonated form assisted by one molecule of water. Abstract : The conversion of ptaquiloside to pterosin B was theoretically studied in aqueous neutral (AN) and acid (AA) media. The decrease of activation enthalpies from 42.0 (AN) to 12.6 kcal mol −1 (AA) supports protic catalysis established earlier. PtQ‐dienone, long assumed as the carcinogenic form of PtQ, is not formed. The spirocyclopropane cleavage occurred early and the calculated electronic spectrum of a PtB‐glucose‐water‐H + complex ( λmax =271.5 nm) matched the experimentally reported value although for a different intermediate.